Jia-Wei-Si-Miao-Yong-An decoction modulates intestinal flora and metabolites in acute coronary syndrome model - Zhao, Ning; Wang, Ying; Ma, Yan; Liang, Xiaoxue; Zhang, Xi; Gao, Yuan; Dong, Yingying; Bai, Dong; Hu, Jingqing (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To study the efficacy of Jia-Wei-Si-Miao-Yong-An Decoction (HJ11) for acute coronary syndrome (ACS) and the effects on intestinal microorganisms and metabolites. Methods: Mice were randomized into model, HJ11 and atorvastatin groups after ACS model was established, given drugs by gavage for 28 d. Echocardiography, serum CK-MB and cTnI were used as observation indexes, and inflammation changes were observed by HE staining of heart tissue and serum IL-2, IL-6, TNF-α and hs-CRP. Gut microbiota composition was analysed via 16S rRNA gene sequencing. Metabolomics technology was used to detect fecal metabolites, performed to find the mechanism for the treatment of ACS with HJ11. Results: The results demonstrated that HJ11 could improve cardiac function and inflammatory in ACS. HJ11 could show the opposite trend in F/B and differentially reversed flora norank_f__Ruminococcaceae、Desulfovibrio、Clostridium_sensu_stricto_1、Adlercreutzia、Staphylococcus、Bacteroides、Prevotella、Rikenellaceae_RC9_gut_group、unclassified_o__Bacteroidales and Ruminococcus_gauvreauii_group at the genus level compared with model group. 23 differential metabolites were confirmed, the main enriched pathways were related with amino acid metabolisms,and ADMA was clearly reported to be associated with cardiovascular disease. Correlation analysis between flora, metabolites and inflammatory factors, and cardiac function found that there is a close relationship between them, the improving ACS effect of HJ11 is associated with specifically altered microbes and metabolic. Conclusion: HJ11 could treat ACS effectively. HJ11 may elevate the beneficial microbes associated with cardiovascular disease or risk factors(Bacteroides and Rikenellaceae_RC9_gut_group), altering metabolites and reducing ADMA levels, thus exerting efficacy in the treatment of ACS.